2017
DOI: 10.31703/grr.2017(ii-i).04
|View full text |Cite
|
Sign up to set email alerts
|

Pakistan Civil-Military Relations in the Context of External Politics

Abstract: Pakistan's military establishment defends its prominent role in the society due to the set of complex threats and a series of conflicts which Pakistan has been facing. At the time of its creation, Pakistan found itself in the midst of instability due to the adverse policies of its rival neighbors. Pakistan has the decisive position in the global power politics. The disconcerting situation develop due to the sense of guardianship. The army believes that the civilian government lacks the vision and political ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…These challenges were caused due to the instability of the economic and political system, which has enhanced the challenges both at the domestic and foreign level, and unfortunately, Pakistani society has to face all of these challenges (Lodhi, 2011). Taj, Rahim & Malik (2017) examined civil-military relations in the context of strategic challenges and suggested that it is vital for Pakistan to have balanced civil-military relations, as it will tag a good name in the international world. Also, for substantial rewards from the international community, it is pertinent that country's leader should think selflessly and objectively.…”
Section: Introductionmentioning
confidence: 99%
“…These challenges were caused due to the instability of the economic and political system, which has enhanced the challenges both at the domestic and foreign level, and unfortunately, Pakistani society has to face all of these challenges (Lodhi, 2011). Taj, Rahim & Malik (2017) examined civil-military relations in the context of strategic challenges and suggested that it is vital for Pakistan to have balanced civil-military relations, as it will tag a good name in the international world. Also, for substantial rewards from the international community, it is pertinent that country's leader should think selflessly and objectively.…”
Section: Introductionmentioning
confidence: 99%